Proposed Marketing Strategy in Suburban Area (Case Study: Hook 88 Coffee & Food) (The Indonesian Journal of Business Administration, 2021)
Coffee shop business is one of the business which have a lot of interest, many business actors, ranging from big cities, small cities to rural areas, are eyeing this industry. Hook 88 Coffee & Food is one of the F&B business brands that offers processed coffee drinks and various foods with industrial rustic place concept. The problem is unstable revenue in 2019 and 2020, this is due to several things. The purpose of this research is to determine the suitable marketing strategy in sub urban area in order to stabilize the revenue. To analyze and research, both methodology, qualitative and quantitative methodology is used to gain information and alternatives for improvement in the business. The primary data gathered is from questionnaire of consumers who came to Hook 88, Competitors analysis, Marketing Mix 7P analysis, STP analysis, Porter’s Five Forces, PESTEL analysis, Pandemic Situation analysis Value Chain analysis, Research Based View using VRIO analysis and SWOT analysis. For analysis technique, descriptive analysis is performed. Based on the analyses, Hook 88 needs to improve marketing strategies to make the revenue stabilize. Customer seek for several facilities and new added value. To resolve the problem of sales issues the company will implementing solutions in marketing and development strategies e.g : keep location and improve several facilities, Provide Several Promotion Program in Social Media, keep the price and build loyalty program, collaborate with social media influencer and another brands, and the time and scheduling to implementing the strategy is using OKR method.Keywords: Coffee shop, Sub urban, Marketing Strategy, SWOT Analysis, OKR method